Factors Related to the Incidence of Hypertension - Reny Marischa Putri; Bambang Setiaji; Ferizal Masra; Endang Budiati (GLOBAL HEALTH SCIENCE GROUP, 2021)
Hypertension is dubbed the silent killer because this disease has no specific symptoms, hypertension can attack anyone, and at any time, and can cause degenerative diseases, to death. According to several studies, people with hypertension are 12 times more likely to have a stroke and 6 times more likely to have a heart attack. Hypertension is usually not realized by the public because the symptoms are not clear and resemble health complaints in general. Patients only find out that they have hypertension after checking their blood pressure, or after the onset of other diseases. Type of research is quantitative, analytical survey research design with Cross Sectional approach. The research population of all residents aged over 45 years who live in Bandar Lampung City based on data from the population and civil registration office of Bandar Lampung city in 2020 as many as 424,183 people, with the Proportional Random Sampling technique as many as 216 people. In this study, researchers used interview techniques using questionnaires. Data analysis used Chi Square statistical test and Logistics Regression. The research was carried out on March 2021. Research result there was a correlation between caffeinee (p-value = 0.022, and OR = 1.951), smoking habits (p-value = 0.017, and OR = 2.006) obesity (p-value = 0.000, and OR = 3.580), physical activity (exercise) (p-value = 0.012, and OR = 2.078) with the incidence of hypertension in Bandar Lampung City in 2021. Obesity variable is the dominant factor that is most related to the incidence of hypertension in Bandar Lampung City in 2021 (p-value = 0.000, and OR = 32,891). This can be done by holding regular counseling at the Posyandu for the elderly and holding regular exercise programs at the Public Health Center, namely doing morning exercises with the community every Friday. Furthermore, leaflets can be distributed about hypertension when exercising at the Public Health Center, as well as posting posters about the importance of maintaining a healthy diet, maintaining an ideal body weight and exercising regularly in places that are easily accessible by the community, such as at the market, at the village hall. or at the community meeting hall.